2005
DOI: 10.1021/np040142x
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Constituents fromBoswelliapapyrifera

Abstract: Phytochemical investigation of the stem bark extract of Boswellia papyrifera afforded two new stilbene glycosides, trans-4',5-dihydroxy-3-methoxystilbene-5-O-{alpha-L-rhamnopyranosyl-(1-->2)-[alpha-L-rhamnopyranosyl-(1-->6)]-beta-D-glucopyranoside (1), trans-4',5-dihydroxy-3-methoxystilbene-5-O-[alpha-L-rhamnopyranosyl-(1-->6)]-beta-D-glucopyranoside (2), and a new triterpene, 3alpha-acetoxy-27-hydroxylup-20(29)-en-24-oic acid (3), along with five known compounds, 11-keto-beta-boswellic acid (4), beta-elemonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 19 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…Interpretation of 1D proton (400 MHz), HSQC and HMBC spectra (Bruker Avance 400, CD 3 OD) indicated that approximately equimolar amounts of 3-O-methyl-(E)-and 3-O-methyl-(Z)-resveratrol 5-Orutinosides were present. The former isomer has been reported from Elephantorrhiza goetzei (Leguminosae) (Wanjala and Majinda, 2001) and Boswellia papyrifera (Burseraceae) (Atta-ur-Rahman et al, 2005). A reexamination of the original crude extract with positive ion APCI-MS revealed an ion peak (m/z 243.1, [M+H] + ) that corresponds to 3-O-methylresveratrol (or its isomer), in addition to the two glycosides.…”
Section: Resultsmentioning
confidence: 93%
“…Interpretation of 1D proton (400 MHz), HSQC and HMBC spectra (Bruker Avance 400, CD 3 OD) indicated that approximately equimolar amounts of 3-O-methyl-(E)-and 3-O-methyl-(Z)-resveratrol 5-Orutinosides were present. The former isomer has been reported from Elephantorrhiza goetzei (Leguminosae) (Wanjala and Majinda, 2001) and Boswellia papyrifera (Burseraceae) (Atta-ur-Rahman et al, 2005). A reexamination of the original crude extract with positive ion APCI-MS revealed an ion peak (m/z 243.1, [M+H] + ) that corresponds to 3-O-methylresveratrol (or its isomer), in addition to the two glycosides.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, the inhibitory action of stilbene glycosides with glucosyl residue at their 3-position toward PDE has been reported. 35) This is the first description of the inhibition of PDE by the stilbene glycoside which has glucosyl residue at its 4′-position.…”
Section: Resultsmentioning
confidence: 98%
“…(found in East Africa), another deciduous, gum-producing, multipurpose perennial tree that grows in Somalia, Ethiopia, Eritrea, Sudan and in the other east African countries, is claimed to have been the source of olibanum in antiquity and produces resin of a quality known as “boido” [4,7,18]. …”
Section: Identification Of Boswellia Speciesmentioning
confidence: 99%
“…Meanwhile, it is also used in the treatment of amenorrhea, menorrhagia, polyuria, scrofula, syphilis, asthma, bronchitis, sores, and diseases of the nervous system [7]. Generally speaking, frankincense is widely used as an anti-inflammatory drug and numerous reports suggest that triterpenoids may be the bioactive ingredients responsible for these properties [6,8].…”
Section: Introductionmentioning
confidence: 99%